Rheological behaviour and microstructure of pea protein/K-carrageenan/starch gels with different setting conditions - Sousa, Isabel (2010)
The aim of this work was to study the rheological properties and microstructure of pea protein/k-carrageenan/starch gels as affected by different cooling conditions. Dynamic oscillatory measurements for mixed gels, cooled at different rates, were conducted in a stress- controlled rheometer in order to clarify the kinetics of gel formation and characterise the structure of the matured gels. Texture parameters were determined from the texture profile analysis using a texturometer. Microstructure was observed using confocal laser scanning microscopy. In order to understand the role of each hydrocolloid on the gel network, rheology of single component gels were also studied. The results showed that gel setting conditions had a significant influence on the phase separation process of pea protein and k-carrageenan, and hence on the final structure and textural properties of the mixed gel. Slower cooling promotes an extensive phase separation between pea protein and k-carrageenan. Consequently, the size of pea protein aggregates was larger at the lowest cooling rate and decreased with increasing cooling rate. At faster cooling, an increase in elastic modulus and texture parameters of the gels were observed. Comparison of cooling and maturation profiles for the mixed system with those obtained for the individual components suggested that the gelation mechanism of k-carrageenan should govern that of the multicomponent gel.